Value at risk modeling in microlending: The case of lending investors around Metro Manila 1999-2002 - Perez, Junette A. (Animo Repository, 2004)
Sustaining lending operations and lending operations management were tackled in this study, 50 lending operators here in Metro Manila and randomly selected borrowers were surveyed to build a profile of both Metro Manila lenders and borrowers. Aside from the survey, five other stages were necessary in the completion of the results. With the help of the probability of loan grant, it was found that it is less likely that a borrower with high income to be granted a small loan amount. In addition, probability of loan default found that a borrower with a guarantor is more likely to default on his loan payment. Using a Value at Risk (VaR) model, this study found that one component of the VaR model, the 91-day forward treasury rates, was insignificant in the VaR model employed.